Level of Environmental Knowledge, Attitude and Friendliness among Secondary School Students in Edo State, Nigeria - Odia, Agnes Anuoluwapo; Aimiyekagbon, Lucky Omoede (NIU Journal of Social Sciences; Vol 11 No 2 (2025): NIU Journal of Social Sciences, Vol. 11 No. 2, June 2025, 2025)
Environmental sustainability has become a global priority, placing increased emphasis on environmental education, especially among students. This paper explored the levels of environmental knowledge, attitudes, and friendliness among secondary school students. It also identifies the sources of environmental information among senior secondary school students in Edo State, Nigeria. Four research questions guided the study. The study adopted survey research design. The population of the study was 21,222 while the sample size comprised 1,202 students drawn from both public and government-approved private senior secondary schools. The multi-stage sampling procedure was used in drawing the sample. An achievement test and a questionnaire were used for data collection. Descriptive statistics such as frequency counts, mean, percentages and ranking were used for data analysis. Findings showed that senior secondary school students in Edo State have high level of environmental knowledge, positive environmental attitude and display a high level of environmental friendliness; and environmental information is mostly gotten from the school followed by the home. It was therefore recommended among others that the school should put more efforts into ensuring that students continue to get environmental information by integrating environmental education related contents across various subjects to further enhance students’ environmental variables. Keywords: Environmental knowledge, Attitude, Friendliness, Environmental information, Edo State